Antimicrobial Susceptibility of Microorganisms Isolated from Surgical Wounds in Perforated Acute Appendicitis at a General Hospital - Hurtado-Guerrero, Gilmar (2026)
Objective: To determine the antimicrobial susceptibility of aerobic microorganisms isolated from surgical wounds of patients with perforated acute appendicitis in a general hospital. Methods: 225 wound culture reports from the fifth postoperative day were reviewed (2017–2021). Samples were processed using the Vitek 2 automated system. Results: 143 strains were isolated from 134 positive cultures. The most frequent bacteria were Escherichia coli (60.8%) and Pseudomonas aeruginosa (21.7%). E. coli: Susceptibility was >90% for carbapenems, amikacin, colistin, piperacillin/tazobactam, and tigecycline, but <11.1% for cephalosporins, fluoroquinolones, and Sulfamethoxazole/trimethoprim. Resistance was due to Extended-Spectrum Beta-Lactamase (ESBL) strains in 88.5% of cases. P. aeruginosa: Susceptible to colistin and aztreonam, but resistant to cephalosporins, carbapenems, fluoroquinolones, and aminoglycosides due to carbapenemases in 44.4% of cases. Conclusion: E. coli (88.5% ESBL+) and P. aeruginosa were the most common microorganisms. E. coli remained susceptible to carbapenems and amikacin, while P. aeruginosa showed high resistance to carbapenems.